PERENCANAAN KEHAMILAN SEHAT PADA CALON PENGANTIN PEREMPUAN YANG BERNIAT MENIKAH USIA DINI DI KABUPATEN SEMARANG TAHUN 2020 - Niki Ayu Kusumaning Pertiwi; Ratih Indraswari; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2021)
One of the factors of the high-risk pregnancy complication is caused by the young age of pregnant women (<20 years old). Lack of knowledge about complications of high-risk pregnancy caused the high number of complication pregnancy cases of adolescent girls in Sumowono, Bandungan, Bergas, and Jambu districts. This research aimed to describe how the practice of healthy pregnancy planning in adolescent girls who get early married. The method of this research was analytic quantitative with a cross-sectional design. The populations were 50 women bride-to-be that less than 19 years old who registered in KUA Sumowono, KUA Bandungan, KUA Bergas, dan KUA Jambu and will marry in August and September 2020. The samples were 50 women bride-to-be were selected using total population sampling. This research used univariate and bivariate analysis. The result of  univariate analysis showed that most of the respondents were aged 18 years old, respondent’s education are a senior high school, respondent’s income is low income, and respondent’s occupation is laborer. The result of the chi-Square test showed that there is a relation between knowledge (p=0.000), attitude (p-value=0.013), and access to information (p-value=0.007) with the practice of healthy pregnancy planning. Meanwhile, there is no relation between family support (p=0.661), health worker support (p=0.490), future husband support (p=0.793), respondents’s age (p=0.302), respondent’s occupation (p=0.058), respondent’s education (p=0.963), respondent’s income (p=0.851), father’s education (p=0.011), mother’s education (p=0.960), father’s occupation (p=0.413), mother’s occupation (p=0.485), father’s income (p=0.902), and mother’s income (p=0.767).